Cardiogenic shock induced by bisoprolol in a patient with CYP2D6 variant. A case report. Issue 4 (April 2015) - Nakayama, Masafumi; Fuse, Koichi; Sato, Masahito; Okabe, Masaaki; Komatsu, Yasushi; Yamashina, Akira; Aizawa, Yoshifusa
Abstract: A 66-year-old man was admitted for congestive heart failure with tachycardiac atrial fibrillation (AF). Heart failure was improved by diuretics, but control of heart rate by verapamil was insufficient, and bisoprolol was prescribed. After taking 2.5 mg of bisoprolol, he developed a general malaise followed by sinus bradycardia and shock. In addition to catecholamines, the patient was treated with intra-aortic balloon pumping and a pacemaker. With intensive therapy, the general condition was improved, and acute elevation of liver enzymes after bisoprolol was normalized by the 17th hospital day. The blood sample taken 30 h after the intake of bisoprolol showed abnormally high levels. Although the patient was CYP2D6*10 heterozygote, the precise mechanism for excess accumulation of bisoprolol and refractory shock remains unknown. <Learning objective: Bisoprolol has been used for heart failure, but it may need caution to avoid hemodynamic deterioration. In our case, refractory shock and acute liver injury were induced by bisoprolol. The blood concentration was excessively high. The patient was CYP2D6*10 heterozygote, but the precise mechanism and shock are to be studied.>